2022
DOI: 10.5217/ir.2021.00139
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical and real-world experience with Crohn’s disease treated with anti-tumor necrosis factor-α antibodies

Abstract: Background/Aims: Although anti-tumor necrosis factor (TNF)-α agents are important therapeutic drugs for Crohn’s disease (CD), data regarding their long-term sustained effects are limited. Herein, we evaluated the long-term loss of response (LOR) to anti-TNF-α agents in patients with CD.Methods: This retrospective study included patients with CD who started treatment with infliximab or adalimumab as a first-line therapeutic approach. The cumulative event-free, retention, and surgery-free rates after the start o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…While treatment strategies for intestinal BD are, in large part, dependent on the physician's discretion, 5 general treatment has been performed in a manner similar to CD, namely, step-up therapy according to disease severity. 2,31,32 Immunosuppressants, including thiopurines, methotrexate, and tacrolimus, are indicated for patients with moderate-to-severe disease activity or corticosteroid dependency. 5,33,34 In our study, more patients in the early-onset group required immunosuppressants than in the adult-onset and late-onset groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While treatment strategies for intestinal BD are, in large part, dependent on the physician's discretion, 5 general treatment has been performed in a manner similar to CD, namely, step-up therapy according to disease severity. 2,31,32 Immunosuppressants, including thiopurines, methotrexate, and tacrolimus, are indicated for patients with moderate-to-severe disease activity or corticosteroid dependency. 5,33,34 In our study, more patients in the early-onset group required immunosuppressants than in the adult-onset and late-onset groups.…”
Section: Discussionmentioning
confidence: 99%
“…24 Clinical disease activity was assessed according to the DAIBD, which consists of eight items: general well-being, fever, EIM, abdominal pain, abdominal mass, abdominal tenderness, intestinal complications, and number of liquid stools, with scores ranging from 0 to 325. Based on calculated DAIBD score, disease severity was classified into four disease groups: quiescent (≤ 19); mild (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39); moderate ; and severe (≥ 75). 25 Typical ulcers were defined as large, oval-shaped, and deep-penetrating ulcers with discrete borders in the ileocecal area.…”
Section: Methodsmentioning
confidence: 99%
“… 19 We previously reported that CRP level at the introduction of anti-TNFα agents is a predictor of reduced therapeutic effects in patients with CD, 26 and that CRP/Alb ratio at 3 months after the introduction of anti-TNFα agents is a predictor of secondary failure. 27 A previous report on patients with CD who started treatment with anti-TNFα agents showed that treat-to-target strategies based on CRP or Alb were useful for preventing hospitalization, surgery, and discontinuation of biological therapy for CD. 28 Thus, a combination of CRP and Alb, which are simple biomarkers, can improve the ability to predict mucosal healing.…”
Section: Discussionmentioning
confidence: 99%
“… 11 - 13 However, a significant proportion of IBD patients treated with intravenous (IV) infliximab experience nonresponse or loss of response (LOR), thus necessitating either a dose escalation of IV infliximab or switching to another biologic/small molecule agent. 14 - 16 Unfortunately, in several countries, including South Korea, the healthcare system or insurance programs do not permit the dose escalation of IV infliximab in such cases (e.g., up to 10 mg/kg every 8 weeks or 5 mg/kg every 4 weeks). Recently, a new subcutaneous (SC) formulation of infliximab, namely, CT-P13 SC, has been developed, 17 and it has shown comparable efficacy and safety with improved acceptability.…”
Section: Introductionmentioning
confidence: 99%